A mission execution decision making methodology based on mission-health interrelationship analysis. (May 2016) - Geng, Jie; Lv, Chuan; Zhou, Dong; Wang, Zili
Highlights: A mission decision making method is presented based on mission–system analysis. The method analyzes the basic interrelationship between mission and modules. The method focuses on the contractive analysis between requirement and capability. This method provides a quantitative suggestion for mission decision making. Abstract: In this paper, a mission execution decision making methodology is proposed based on the interrelationship between mission requirements and system capability. A mission–system correlation model is established after analyzing mission–function and function–system separately to determine the connections between mission and system. A detailed contrastive analysis between mission requirements and system capability, including transforming intrinsic health into mission health and modules interrelationship analysis, is then conducted for the given mission, which provides quantitative suggestions for objective and timely mission-execution decision making. A case study on a cruise is used to illustrate the performance of the methodology.